Inequality, democracy, institutional quality, and fiscal redistribution - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2007)
This paper studies the joint effect of economic and political inequalities on redistributive taxation and institutional quality. The theoretical model suggests that income inequality, coupled with political bias in favor of the rich, decreases redistribution and lowers institutional quality. The effect of the former is to increase productive investment, and the effect of the latter is to decrease it - with resulting ambiguous implications for economic growth. Testing these predictions empirically in a panel of countries, the paper finds that inequality has a negative effect on both institutional quality and redistribution, especially in non-democratic countries.
Keywords: D31; D90; E62; H11; O11; 330; Inequality; institutions; redistribution; Einkommensverteilung; Soziale Ungleichheit; Einkommensumverteilung; Institutionelle Infrastruktur; Theorie; Welt